Historical fluctuations and recent observations of Northern Anchovy Engraulis mordax in the Salish Sea. (January 2019) - Duguid, William D.P.; Boldt, Jennifer L.; Chalifour, Lia; Greene, Correigh M.; Galbraith, Moira; Hay, Doug; Lowry, Dayv; McKinnell, Skip; Neville, Chrys M.; Qualley, Jessica; Sandell, Todd; Thompson, Matthew; et al.
Abstract: Many small pelagic fish species exhibit dramatic fluctuations in abundance accompanied by range expansions during periods of favorable environmental conditions. The location and extent of suitable habitats also shift in response to both short term variability and long term trends in climate. Near the margins of a contemporary range, trends in abundance may reflect a continuation of historical variability but may also foreshadow future changes in distribution. The Salish Sea (all inland marine waters of Washington State and southern British Columbia; made up of the Strait of Georgia, Strait of Juan de Fuca, and Puget Sound) is a highly productive estuarine system at the northern end of the distribution of Northern Anchovy ( Engraulis mordax ). An apparent recent (2014–2016) increase in Northern Anchovy abundance has generated interest in the dynamics of this species in the Salish Sea. We compiled recent and historical data to understand spatiotemporal patterns of distribution and fluctuations in abundance over the last century. Spatially-consistent occurrence of eggs, larvae, and juveniles, and year-round presence of multiple age classes, confirm that successful spawning and recruitment of Northern Anchovy occurs within the Salish Sea. Most periods of elevated Northern Anchovy abundance in the last century have corresponded to, or lagged, periods of elevated ocean temperatures. While a 2005 peak in abundance within the Salish Sea also corresponded to higher abundance of Northern Anchovy in adjacent regions of the coastal Pacific Ocean, it seems unlikely that Salish Sea abundance is controlled primarily by advection or migration from external populations. Persistence of elevated ocean temperatures like those observed from 2014 to 2016 could lead to consistently high abundance of Northern Anchovy within the Salish Sea, with implications for trophic relationships and ecosystem function.